Teachers' Knowledge and Stigmatizing Attitudes Associated With Obsessive-Compulsive Disorder: Effectiveness of a Brief Educational Intervention - Chaves, Antonio; Arnáez, Sandra; Roncero, María; García-Soriano, Gemma (Frontiers in Psychiatry, 2021)
Because children and adolescents are vulnerable to developing obsessive-compulsive disorder (OCD), classroom teachers play an important role in the early identification and intervention in students with OCD. The present study aims to explore the recognition of OCD, general knowledge about this disorder, implications in the classroom, and stigmatizing attitudes among teachers, as well as the effectiveness of a brief educational intervention about OCD. Participants (n=95; mean age=43.29 years old; 64.3% female) were primary and secondary school teachers who were randomly assigned to an experimental group or a control group. All of them completed a set of self-report questionnaires, read an educational fact sheet (either about OCD in the experimental group or about a healthy diet in the control group), and again completed the questionnaires. Results show that prior to the intervention, most of the teachers identified the contamination and order OCD symptoms described in a vignette as specific to OCD (82.1%) and would recommend talking about the problem (98.9%) and seeking help (94.7%). However only a few (36.8%) knew about the most effective OCD treatments or identified compulsions as a main OCD symptom (33%). Moreover, only about half of the teachers correctly identified OCD’s possible interference in classroom routines, such as delays to achieve perfection or concentration problems, and strategies for dealing with OCD, such as continuing with the class rhythm. Stigma levels were from low to moderate. After the brief educational intervention, participants in the experimental group increased their knowledge about OCD, improved their strategies for managing a student with OCD symptoms, and had fewer stigmatizing attitudes associated with pity (p < .05). These changes were not observed in the control group. We can conclude that this brief and easy-to-administer intervention is an effective educational intervention to significantly improve teachers’ knowledge and attitudes, at least in the short-term. These results are especially relevant because OCD is associated with high interference and long delays in seeking treatment, and teachers have a unique opportunity to help with prevention, early identification, and recommending an adequate intervention for OCD.